An injectable molecular hydrogel assembled by antimicrobial peptide PAF26 for antimicrobial application. Issue 53 (1st October 2019) - Cao, Fengyi; Mei, Lin; Zhu, Genxing; Song, Meng; Zhang, Xueli
Abstract : A hexa-antimicrobial PAF26 peptide was investigated to form a self-assembled hydrogel. The hydrogel was injectable and had an outstanding antimicrobial ability. Abstract : Wound infection is a crucial factor that inhibits wound recovery. A feasible measure to solve this problem is using antimicrobial biomaterials to suppress the microbial growth. In this work, an amphipathic antimicrobial peptide (Ac-RKKWFW-NH2, PAF26) was investigated to form the antimicrobial hydrogel. Triggered by pH, PAF26 peptide could self-assemble into a hydrogel, and the hydrogel formed was injectable and exhibited shear-thinning ability. Antimicrobial experiments demonstrated that the self-assembled hydrogel had an outstanding antimicrobial ability against pathogenic microbes such as Candida albicans, Staphylococcus aureus, and Escherichia coli via destroying the cell membrane structure. Thus, this study provides a novel method for preparing an injectable antimicrobial peptide hydrogel for antimicrobial therapies.